Radical gastrectomy for D2 distal gastric cancer - Dong, Ping (Chinese Journal of Cancer Research, 2013)
The patient is a 56-year-old man who visited our hospital for “repeated epigastric pain for more than two months.” Physical examination showed nearly pale appearance; abdomen was soft and no mass palpable; left supraclavicular lymph node (-); and digital rectal examination (-). Gastroscopy revealed a bulging ulcerative lesion of the antrum at the lesion lesser curvature side, which had dirty appearance and was solid, fragile and prone to bleeding. Ultrasonic gastroscopy suggested myometrial invasion. Biopsy indicated adenocarcinoma.